The Future of Water in African Cities : Why Waste Water? - Jacobsen, Michael; Webster, Michael; Vairavamoorthy, Kalanithy (Washington, DC: World Bank, 2012)
The overall goal of this book is to change the way urban policy makers think about urban water management, planning, and project design in Africa. African cities are growing quickly, and their current water management systems cannot keep up with growing demand. It will take a concerted effort on the part of decision makers across sectors and institutions to find a way to provide sustainable water services to African city dwellers. This book argues that these complex challenges require innovative solutions and a management system that can work across institutional, sectoral, and geographic boundaries. A survey conducted for this analysis shows that African city leaders and utility operators are looking for ways to include a broader range of issues, such as water resources management, flood and drought preparation, rainwater harvesting, and solid waste management, than previously addressed in their water management plans. This book argues that integrated urban water management (IUWM) will help policy makers in African cities consider a wider range of solutions, understand water's interaction with other sectors, and secure resilience under a range of future conditions.